KONEKSI MATEMATIK SISWA MTS KELAS VIII PADA MATERI SEGITIGA - Ningrum, Nadya Sukma; Rohaeti, Euis Eti; Afrilianto, M (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The research aims to know the mathematical connections of students of class VII on the material triangle. The method used is descriptive with the metacognitive approach. The subject of this research is class VII MTs DAARUL MA'ARIF. The result of data analysis shows students of class VII MTs on material triangle still low. This can be know at the time students do the questions, or practice in everyday life. From the results of the percentage of 5 students only 45% knowledge about the material triangle.